Nursing Care Plan for Patients with Tay–Sachs—A Rare Paediatric Disease. - Cortés-Martín, Jonathan; Piqueras-Sola, Beatriz; Sánchez García, Juan Carlos; Reinoso-Cobo, Andrés; Ramos Petersen, Laura; Díaz-Rodríguez, Lourdes; Rodríguez-Blanque, Raquel (MDPI, 2023)
Tay–Sachs disease is classified as a rare paediatric disease of metabolic origin. It is an autosomal recessive inherited disease. The gene responsible for the disease is known as HEXA, and it is located on chromosome 15(15q23). There is currently no effective treatment for Tay–Sachs disease; hence, it is an incurable disease in which patients do not live for more than five years, meaning that nursing care takes on greater importance to maintain quality of life. The main objective of this work is to develop a specific standard nursing care plan by applying an inductive research method supported by nursing methodology using the NANDA-NIC-NOC taxonomy and validated by the Delphi method. This care plan will improve the knowledge of health professionals on this topic and support future studies on the disease. Following its implementation, the care plan proposed in this study aims to increase the quality of life of patients diagnosed with this disease.
Keywords: Tay-Sachs, Enfermedad de; Enfermería pediátrica; Cuidados de enfermería; Rare disease; Tay–Sachs; Nursing care plan; Clinical practice; Healthcare; Delphi method